Hubungan Konsumsi Lemak dan Natrium Makanan Cepat Saji dengan Tekanan Darah pada Usia Dewasa di Wilayah Kerja Puskesmas Telaga Dewa Kota Bengkulu - Zelika Nabila Putri; Desri Suryani; Risda Yulianti (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2026)
High blood pressure is a global health problem with increasing prevalence and is associated with sodium, fiber, and fat. The high consumption of fast food is a serious public health concern, primarily due to the unbalanced nutritional composition of fast food. Fast food is very high in saturated fat and sodium. High sodium content contributes to increased body fluid volume, which can trigger hypertension, while saturated fat contributes to atherosclerosis, or narrowing of the arteries. To analyze the relationship between fat and sodium consumption from fast food and blood pressure in adults in the Telaga Dewa Community Health Center (Puskesmas) in Bengkulu City. This study used a cross-sectional design, with a sample size of 61 adults (21–65 years old) selected through purposive sampling. Data were analyzed using a correlation test. The average fat consumption of respondents was 52.7 g, and sodium consumption was 763.1 g. The average systolic blood pressure was 127 mmHg, and diastolic blood pressure was 85 mmHg. The analysis showed a significant association between fat consumption and blood pressure (p=0.000) and between sodium consumption and blood pressure (p=0.000). Consumption of fat and sodium in fast food is related to blood pressure, showing a strong relationship, meaning that the higher the intake of fat and sodium, the greater the tendency for increased blood pressure. There is a relationship between showed a significant association between fat consumption and blood pressure, so sodium and blood pressure.